KARAKTERISTIK PENDERITA HIPERTENSI DENGAN STROKE YANG DIRAWAT INAP DI RUMAH SAKIT UMUM KABANJAHE TAHUN 2011-2015 - elen dinarta naibaho; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT Non Communicabke Disease (NCD) is the priming cause of death globally. Hypertension is called as The Silent Killer Disease, if it cant be controlled, will envolve and give rising to complication which are Coronary Disease, Chronic Renal Failure (CRF), and Stroke. Hypertension was the biggest cause death of stroke (51%), while coronary disease (45%). In Indonesian the highest prevalence complication of hypertension is stroke (12,1%), then coronory disease (1,5%), CRF (0,2%) (In Kemenkes RI, 2015). The objective study is to know the characteristic of patient Hypertension with Stroke which was hospitalized at Kabanjahe General Hospital in 2011-2015. This study was adopted descriptive research with case series design. The population was as same as with the sample were 115 patients. The result of this study obtained that the highest proportions of suffers result in the age group ≥ 55 years old (72,2%), sex woman (51,3%), Protestant (62,5%), farmer (45,2%), married (80,0%), degree 2 (62,6%), stroke non haemorragic (70,4%), hemiparese sinistra (54,8%), the length of average treatment was 6,99 days, and coming home condition was by PBJ (74,8%). There are no significant differences between the age based on the degree of hypertension (p=0,382), type of stroke (p=0,062), between sex based on the degree of hypertension (p=0,257), type of stroke (p=0,772),between degree of hypertension based on the coming home condition (p=0,501), there is a significant differences between type of stroke based on the coming home condition (p=0,008), and between type of stroke based on the degree of hypertension (p=0,005). Recommended to the staff of Kabanjahe General Hospital to give conseling to the family of the patients  about the real condition of the patients, the risky factors of Hypertension with Stroke and the preventions of it that can be done, and write medical record data such as family history of disease, smoking or not. Keywods : Hypertension of Stroke, Characteristic of patients